A behavioral and serological survey on HIV prevalence among prisoners in Benin - HESSOU, Septime; DOUGNON, Victorien; GLELE AHANHANZO, YOLAINE; IMOROU, Ali; AHOUSSINOU, Clément; LEGBA, B; ZANNOU, Marcel D.; BABA MOUSSA, Lamine (My University, 2017)
Cases of HIV are common in Benin, with infection rates varying according to socioeconomic and cultural factors, and by region. Certain segments of the population, such as prison inmates, sex worker clients and truck drivers are at high risk for HIV/AIDS. The aim of this study is to identify which behavioral and serological indicators contribute to the spread of HIV among prisoners. A total of 496 inmates from prisons located in all major cities in Benin were surveyed. Data was collected through interview sessions carried out using a questionnaire and through blood samples. The results show that most inmates are Beninese (83.5%), and the average age is 33 years (range: 14-80 years). No prisoner reported using a condom the last time they engaged in sexual intercourse. Blood exposure was found in 14.6% of inmates and HIV was detected in 1.4% of cases. Our analysis indicates that the length of detention and gender are factors that influence HIV status. However, age, education, nationality and HIV awareness had no significant effect on HIV prevalence among inmates. The results highlight the need to raise awareness in prisons about HIV. This can be achieved by strengthening communication strategies and by organizing HIV and sexually transmitted diseases information sessions for both prison officers and inmates.
Keywords: HIV; prisoners